R2D2: An effective model to incorporate ICTs in the EFL classroom? - Cinthya Olivares Garita; Verónica Brenes Sánchez; Evelyn Valverde Marín (Universidad de Costa Rica, 2020)
Information and Communication Technologies (ICT) in English language teaching have become effective tools to boost meaningful learning. In an EFL environment, the need to apply a model to incorporate web tools and free apps in the classroom takes prominence for teachers at the university level. The present study is an attempt at determining the effectiveness of the implementation of the Read-Reflect-Display and Do (R2D2) model by Bonk and Zhang (2006) through the design and application of a booklet of activities used by a group of 14 students of the Associate's program in English and 17 students of the Bachelor's degree in English Teaching at Universidad Nacional, Brunca Branch. Due to its nature, this research encompasses a case study with a descriptive scope. The design and implementation will be analyzed through an empirical predictive and retrospective evaluation considering the administration of a teacher and a student questionnaire and a focus group. The instruments were administered to 31 students and 7 teachers. The results of the analysis led to conclude that the model implemented in a booklet of activities can be effective to integrate ICTs and innovate in both the techniques used to incorporate technology and the pedagogical materials EFL teachers bring to the classroom only if teachers open up to new ideas and keep abreast of the constant technological changes that education and society demand.